Fantasy and functionality : Surveying personal italo disco related musical experience as a metaphoric-affective conceptualization process - Mertsalo, Sami (My University, 2020)
In this thesis, I study personal musical experience in the light of so-called embodied cognition. According to this research paradigm, meaning arises from our interaction with the physical world in a process where the human body has a mediating role. The process has been shown to be metaphorical by nature, due to which I base my introspective findings mostly on the conceptual metaphor theory (CMT) of Lakoff & Johnson. Interaction with environment invokes affects, which has consequences in terms of person’s preference for metaphoric content. The goal of my work is to investigate reasons for my penchant for certain kind of music. Addressing this involves scrutinising my own perceptions and feelings when listening to italo disco, thus, music that I like, and supporting the findings with theories and earlier research. Besides CMT and also traditional music analysis, I utilise, for example, the complementary theories of the sonic object and musical gestures in pointing out experiential entities from textural and timbral elements of an italo disco song. The entities (sonic objects) are expected to arise from an affective sensation of motion, a process where conceptual metaphor plays an important role. Therefore, at the second stage of the analysis, I demonstrate metaphors on the grounds of the sonic objects in an attempt of establishing at least a part of my personal “metaphorical repertoire”. Arnie Cox’s mimetic hypothesis and framework for the study of musical affect is applied particularly during the second part of the analysis. The results of the inquiry confirm my hypothesis about the central role of conceptual metaphor in the emergence of (personal) musical experience. The set of metaphors I succeeded to point out suggest that I’m inclined to music that communicates powerful and energetic, thus clearly arousing affects–music that responds to the need of indulging in fantasy.

Tutkin työssäni yksilöllistä musiikkikokemusta niin sanotun kehollisen kognition paradigman kautta. Tämän lähestymistavan mukaan merkitykset syntyvät vuorovaikutuksessa fyysisen maailman kanssa. Keholla on tässä prosessissa välittävä rooli. Prosessi on osoittautunut metaforiseksi, minkä vuoksi pohjaan introspektiiviset havaintoni pääasiassa Lakoffin & Johnsonin käsitteelliseen metaforateoriaan. Ympäristön kanssa vuorovaikutuksessa oleminen herättää affekteja, millä on vaikutusta siihen, minkälaisen metaforasisällön henkilö laittaa etusijalle. Työni tavoitteena on tutkia syitä musiikkimieltymyksiini. Metodina käytän omien aistimusteni ja tunteideni tarkkailua kuunnellessani italodiskoa–musiikkia, joka vetoaa minuun. Tuen introspektion tuloksia eri teorioilla sekä aiemmalla tutkimuksella. Käsitteellisen metaforateorian ja esimerkiksi perinteisen musiikkianalyysin lisäksi käytän muun muassa niin sanotun ääniobjektin ja musiikillisten eleiden teorioita pyrkiessäni osoittamaan kokemusperäisiä kokonaisuuksia italodiskokappaleen tekstuurisista ja äänenvärillisistä osatekijöistä. Kokonaisuuksien (ääniobjektien) voidaan olettaa syntyvän affektiivisen liikkeen aistimuksen pohjalta. Tässä prosessissa käsitteellinen metafora on tärkeässä roolissa. Siksi analyysin toisessa vaiheessa osoitan ääniobjekteihin pohjautuvia käsitteellisiä metaforia tarkoituksenani esitellä osa henkilökohtaisesta ”metaforarepertuaaristani”. Arnie Coxin mimeettistä hypoteesia ja musiikillisen affektin viitekehystä sovelletaan varsinkin analyysin toisessa vaiheessa. Tutkimuksen tulokset vahvistavat hypoteesini käsitteellisen metaforan keskeisestä roolista (henkilökohtaisen) musiikkikokemuksen synnyssä. Osoittamani metaforakokoelma viittaa viehtymykseeni voimakkaita ja energisiä, selvästi kiihottavia affekteja viestivää musiikkia kohtaan–musiikkia, joka mahdollistaa heittäytymisen fantasian maailmaan.
Keywords: italo disco, italo-disco, embodiment, embodied cognition, conceptual metaphor, metaphor, image schema, affect, mimesis, sonic object, sound object, musical gesture, gesture, EDM, italodisko, italo-disko, kehollisuus, kehollinen kognitio, käsitteellinen metafora, metafora, mielikuvaskeema, affekti, affektiivisuus, ääniobjekti, musiikillinen ele, eleet, diskomusiikki